2017
DOI: 10.1002/pon.4347
|View full text |Cite
|
Sign up to set email alerts
|

Information needs of the Chinese community affected by cancer: A systematic review

Abstract: Failing to meet the information needs of the Chinese community members affected by cancer increases the risk for poor cancer outcomes. Potential interventions such as translated resources, bilingual advocates, an online information portal, and communication aids can be helpful in addressing the unmet needs for this community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 54 publications
12
22
0
Order By: Relevance
“…Indeed, this finding is not unique to our study sample. A systematic review of studies on Chinese populations found that the HSI is the most commonly reported needs, with a pooled prevalence of 43.01% [45]. Similar to previous studies in Hong Kong [6,8], the primary unmet need in the present study was having one member of the hospital staff with whom to talk about all aspects of one's condition, treatment and follow-up.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, this finding is not unique to our study sample. A systematic review of studies on Chinese populations found that the HSI is the most commonly reported needs, with a pooled prevalence of 43.01% [45]. Similar to previous studies in Hong Kong [6,8], the primary unmet need in the present study was having one member of the hospital staff with whom to talk about all aspects of one's condition, treatment and follow-up.…”
Section: Discussionsupporting
confidence: 78%
“…The above studies suggest that unmet information needs may be a universal challenge, regardless of migration status. This is confirmed by systematic review findings, which indicated that information needs did not differ between Chinese natives (i.e., Hong Kong, China, Taiwan, and Singapore) and migrants (i.e., Australia and the United States) …”
Section: Introductionsupporting
confidence: 72%
“…There was also a level of frustration with not being able to use their native language (Arabic) to communicate their message directly with HCPs. Our findings are consistent with other studies which report migrants,[ 20 28 ] including Arab cancer survivors,[ 21 29 ] with low English language proficiency, being deterred from seeking health information. This was evident in this study with participants stating that language was a barrier to seeking information about cancer-support groups and participating in cancer workshops.…”
Section: Discussionsupporting
confidence: 93%
“…Immigrants who are not proficient in the dominant language of their host country often struggle to communicate with HCPs and have poorer health outcomes. [ 20 ] This is particularly true for immigrant cancer survivors who have a poorer quality of life, worse psychological status, and higher unmet supportive care needs than other cancer survivors, with communication barriers and lack of access to health professionals who speak their language accounting for most of these needs. [ 21 ]…”
Section: Introductionmentioning
confidence: 99%